2019
DOI: 10.1002/jccs.201900072
|View full text |Cite
|
Sign up to set email alerts
|

Immunoassay of plasmonic gold‐nanoparticle clusters: Plasmon coupling effects for Parkinson biomarker detection

Abstract: A simple signal‐on plasmonic optical assay for the detection of the Parkinson biomarker using gold‐nanoparticle clusters (AuNCs) for signal amplification is presented. This approach is based on the improvement of the optical density (OD) change of the plasmonic band of a localized surface plasmon resonance (LSPR) Au nanoparticle (AuNP) sensor interface using Au NCs conjugated antibodies. The amplification results in a 260‐fold improvement in concentration detection, from 1,000 ng/mL (unlabeled antibody) to 3.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The comparison with the other LSPR-based sandwich immunoassay sensing studies is shown in Table . Various types of LSPR sensors (the X part shown in the table), including the AuNPs immobilized on a glass surface, , the FO-LSPR biosensor, and the Au nanostrip, were compared with the AuNM chip. The AuNM chip possesses an ordered nanostructure array on a flexible PC substrate and shows excellent LODs.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison with the other LSPR-based sandwich immunoassay sensing studies is shown in Table . Various types of LSPR sensors (the X part shown in the table), including the AuNPs immobilized on a glass surface, , the FO-LSPR biosensor, and the Au nanostrip, were compared with the AuNM chip. The AuNM chip possesses an ordered nanostructure array on a flexible PC substrate and shows excellent LODs.…”
Section: Resultsmentioning
confidence: 99%
“…The progressive neurodegenerative disease Parkinson's disease (PD) is the second most common neurological disorder after AD and leads to symptoms including tremors, autonomic disorders, muscle rigidity, and dyskinesia due to loss of dopaminergic neurons in the substantia nigra [75][76][77][78][79]. Sensitive and accurate PD biomarker detection may be critical for tracking PD progression, prognosis, and treatment response.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Sensitive and accurate PD biomarker detection may be critical for tracking PD progression, prognosis, and treatment response. As an example, Ko et al developed a simple and rapid plasmonic immunoassay for the detection of the PD biomarker α‐synuclein antibody in 2019 [79]. In their project, the authors developed AuNP clusters as label‐free biosensors that provided signal amplification for sensitive biomarker detection.…”
Section: Plasmonic Nanoprobes For Chronic Neurological Disorder Bioma...mentioning
confidence: 99%
“…To address the above challenges, efforts have been made to increase optical density by self-assembly of Au NPs. For example, immunoassay probes with enhanced optical density have been reported by forming clusters of Au NPs, , adsorbing Au NPs onto the surface of silica, magnetic particles, and polystyrene particles, , and depositing Au NPs by electrodeless plating. However, in these reports, sufficiently enhancing optical density has been challenging as a result of the sparse distribution of Au NPs on the particle surfaces.…”
Section: Introductionmentioning
confidence: 99%